Synthesis Report of Workshop on Assessing the Impact of Policy-oriented Social Science Research in Scheveningen, The Netherlands November 12-13, 2001 - Ryan, James G. (International Food Policy Research Institute, 2002)
Economists have engaged for some time in developing methodologies for assessing the economic impact of agricultural research and in undertaking empirical studies to measure this impact. In recent years, they have documented more than 1,800 estimates of rates of return to agricultural research. Economists have paid little attention, however, to how to evaluate the impact of social science research. A symposium conducted by IFPRI in 1997 was one of the first attempts to address this knowledge gap. In November 2001, the Netherlands Ministry of Foreign Affairs and IFPRI brought together a group of researchers to follow up on the earlier symposium. Their conclusions fell into two broad categories: how to measure or value the economic impact of policy-oriented social science research and how to enhance the effectiveness of such research in policymaking environments.A number of lessons emerged from the workshop for donors, governments, and researchers about how to enhance the effectiveness of policy-oriented social science research. Donors and governments should: encourage the development of independent, well-managed, high-quality policy research institutions; improve the linkages between research and policy formulation; and invest in studying the policy processes, training, and promoting economic literacy. Research institutions should: know what impacts donors value; ensure that the impacts of value to donors coincide with those of the people and their governments; make ex ante and ex post impact evaluation a part of their core business; create incentive and reward systems consistent with the policy objectives of the agencies that commission or make use of research outputs; undertake more multidisciplinary research on evaluating and enhancing impact, including policy processes; build policy epistemic communities involving all stakeholders; and never compromise on quality and objectivity in the quest for impact. Because much remains to be learned about evaluating the impact of policy-oriented social science research, the workshop participants concluded that IFPRI should take the lead in developing a consortium to help improve interdisciplinary methods of assessing impact. The consortium would consist of institutions, donors, and individuals and would work in partnership with developing countries. Institutions could learn from each other about best practices and in the process exploit synergies, thereby increasing effectiveness and reducing the costs of what is an expensive undertaking. -- Authors' Abstract."